Sosialisasi Produk dan Pengelolaan Keuangan Usaha Mikro Kue Tradisional “Puji Lestari“ di Menur Pumpungan Kota Surabaya - Mataji Mataji; Sigit Santoso (Jurnal Pelayanan Masyarakat, 2025)
Since the implementation of the ASEAN Economic Community (AEC) at the end of 2015, all economic actors—including SMEs and microenterprises—are expected to improve and adapt in order to enhance the quality of both goods and services. Failure to do so may result in Indonesia becoming a "soft target" market for other ASEAN countries, given its status as the most populous country in the region with over 270 million people. SMEs and microenterprises, which represent the embodiment of people-based economic democracy, would be particularly vulnerable if goods and services from various ASEAN countries continue to flood the Indonesian market. Recognizing this situation, empowering SMEs and microenterprises is not only necessary but inevitable to help the nation discover its identity through the development of comparative and competitive advantages. This activity began by identifying existing problems, followed by determining suitable solutions. The method used involves training and mentoring.The outcome of this initiative is the improved capability of the traditional cake microenterprise to optimize its sales by using locally sourced raw materials. As a result, the "Puji Lestari" Traditional Cake Microenterprise has successfully enhanced its production capacity and business management.Financial reporting is also a crucial aspect of business development. A well-maintained financial report reflects the progress of the business, particularly through the net profits it generates. These outcomes serve as indicators of increased empowerment and the strengthening of the enterprise.